The Endocannabinoid System in the Retina: From Physiology to Practical and Therapeutic Applications - Thomas Schwitzer; Raymund Schwan; Karine Angioi-Duprez; Anne Giersch; Vincent Laprevote (Neural Plasticity)
Cannabis is one of the most prevalent drugs used in industrialized countries. The main effects of Cannabis are mediated by two major exogenous cannabinoids: ∆9-tetrahydroxycannabinol and cannabidiol. They act on specific endocannabinoid receptors, especially types 1 and 2. Mammals are endowed with a functional cannabinoid system including cannabinoid receptors, ligands, and enzymes. This endocannabinoid signaling pathway is involved in both physiological and pathophysiological conditions with a main role in the biology of the central nervous system. As the retina is a part of the central nervous system due to its embryonic origin, we aim at providing the relevance of studying the endocannabinoid system in the retina. Here, we review the distribution of the cannabinoid receptors, ligands, and enzymes in the retina and focus on the role of the cannabinoid system in retinal neurobiology. This review describes the presence of the cannabinoid system in critical stages of retinal processing and its broad involvement in retinal neurotransmission, neuroplasticity, and neuroprotection. Accordingly, we support the use of synthetic cannabinoids as new neuroprotective drugs to prevent and treat retinal diseases. Finally, we argue for the relevance of functional retinal measures in cannabis users to evaluate the impact of cannabis use on human retinal processing.